The Role of Green Entrepreneurial Orientation and Self-Efficacy to Encourage Student Intention in Green Entrepreneurship - Jovita Aurellia; Kartika Nuringsih (International Journal of Application on Economics and Business, 2023)
Aligning with achieving sustainable development goals (SDGs), the entrepreneurship sector has a responsibility to synergize between the economic goals and environmental goals through implementing the model of green entrepreneurship. This study develops a model involving green entrepreneurial orientation and self-efficacy to improve the student intention in green entrepreneurship. Totally 180 students from the Economics & Business Faculty of Universitas Tarumanagara Jakarta are taken as respondents. The regression approach is used to analyze the data with the result as follows: the green entrepreneurial orientation owns the higher impact on green entrepreneurship intention, while the impact of self-efficacy is lower than this entrepreneurial intention. Based on this result, supporting of university needs to realize students in developing their business ideas in line with the effort to preserve the environment in the future. It is relevant to achieving the target of SDGs in 2030. The double bottom line orientation is perceived strongly by respondents. Through entrepreneurial learning, educational institutions together with stakeholders could contribute to building mechanisms to improve the education programs in green entrepreneurship. The next study can involve the legal aspect for supporting the sustainability of the green business.